Thermochromic Polyvinyl Alcohol‐Iodine Hydrogels with Safe Threshold Temperature for Infectious Wound Healing (Adv. Healthcare Mater. 18/2021). Issue 18 (22nd September 2021) - Miao, Zhaohua; Sun, Yanbin; Tao, Zhenchao; Chen, Yu; Ma, Yan; Zhu, Dongdong; Huang, Xiang; Zha, Zhengbao
Abstract : Antibacterial Hydrogels In article number 2100722 by Zhengbao Zha and co‐workers, a blue polyvinyl alcohol‐iodine hydrogel with thermochromic and laser‐triggered liquefaction properties, originated from the dynamic interaction between iodine and polyvinyl alcohol, is explored as an effective alternative to conventional iodophor for safe and controllable management of multidrug‐resistance bacterial‐infected open wounds.